Development of Creative Abilities of Preschool Children through Didactic Games - Dilshoda Atabaeva (International Journal on Economics, Finance and Sustainable Development, 2022)
This article discusses the effectiveness of didactic games with theoretical representations in the development of preschool children's creative abilities, as well as their low-level diagnosis and psychology.